Increasing Professionalism Through Effective Business Communication Training in the Digital Era at the Merah Putih Village Cooperative, STM Hulu District, Deli Serdang Regency - Elly Romy; Mei Lisa (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This training is expected to improve the knowledge and skills of cooperative administrators and members in implementing effective business communication, utilizing digital technology as a communication medium, as well as building a professional work culture, improving service quality, strengthening relationships with stakeholders, and supporting the realization of independent, modern, and competitive cooperatives in the digital era. The method used in this activity is a participatory training method that combines material delivery, discussion, practice, and evaluation. This service was carried out in the red and white village cooperative of STM Hulu Kecematan STM Deli Serdang Regency. This service will be held on May 9, 2026. The results of this activity show that effective business communication training can be one of the strategies for human resource development in the cooperative environment. Professionalism is not only determined by technical ability in managing a business, but also by the ability to communicate effectively with various parties. Therefore, improving communication competence needs to be carried out on an ongoing basis so that the Merah Putih Village Cooperative, STM Hulu District, Deli Serdang Regency is able to develop into a modern, professional, and competitive organization in the digital era